1997
DOI: 10.1007/bf02446851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypogeomagnetic field on tissue and intracellular reorganization of mouse myocardium

Abstract: Structural remganization of the myocardium is observed in CBA mice under conditions of hypogeomagnetic field (reduction by 10 s times). Changes in tissue architectonics manifest themselves in a reduced capillary/cardiomyocyte volume ratio against the background of hemodynamic disturbances. Intracellular disturbances result from impaired regeneration processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Mn SOD is located in the mitochondrial matrix (Zhu and Scandalios, 1995 ). It has been shown that mitochondrion is sensitive to the HMF (Fu et al, 2016 ; Belyavskaya, 2004 ; Nepomnyashchikh et al, 1997 ). Based on our data, no significant difference was detected on the expression and activity of Mn-SOD between the GMF and HMF groups; while the denaturation of CuZn-SOD was directly accelerated by the HMF in the solution, a cell-free condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mn SOD is located in the mitochondrial matrix (Zhu and Scandalios, 1995 ). It has been shown that mitochondrion is sensitive to the HMF (Fu et al, 2016 ; Belyavskaya, 2004 ; Nepomnyashchikh et al, 1997 ). Based on our data, no significant difference was detected on the expression and activity of Mn-SOD between the GMF and HMF groups; while the denaturation of CuZn-SOD was directly accelerated by the HMF in the solution, a cell-free condition.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria is closely related to the regulation of reactive oxygen species (ROS) (He et al, 2016 ), which has been proposed as the organelle most sensitive to environmental magnetic field (Belyavskaya, 2004 ). The HMF inhibits mitochondrial function in mouse myocardium and primary muscle cells (Fu et al, 2016 ; Nepomnyashchikh et al, 1997 ). By using transcriptome profiling, we found that the differentially expressed genes in the HMF-exposed human neuroblastoma SH-SY5Y cells were involved in the process of metabolism and oxidative stress (Mo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, HMC caused an increase in heart rate in Danio renio fish embryos [48]. In mice, changes in the tissue and cellular structure of the myocardium occur [84].…”
Section: Cardiovascular System and Immunitymentioning
confidence: 98%
“…Suppression of the innate immune system should also be expected [82]. Changes in the cardiovascular system are also possible, and changes may affect the architecture of the heart tissue itself [44,84]. On the part of the central nervous system, architectural changes may also occur caused by a slowdown in neuronal differentiation [107].…”
Section: Potential Effects Of Hmc On Organisms Depending On Inductionmentioning
confidence: 99%